Neural bases underlying numerical cognition - Dowker, AD (SAGE Publications, 2024)
This chapter deals with the cognitive neuroscience of nonverbal numerical cognition – subitizing and approximate magnitude representation – which are likely to lie at the foundations of numerical cognition, with the understanding of number symbols, and the level of relationship to nonsymbolic number processing, symbolic arithmetic, with spatial representation of number, with the distinctions between factual, procedural and conceptual knowledge of numbers and arithmetic, with processing of multi-digit numbers, and with models of transcoding. Several specific areas are not the main focus of the present chapter, including individual, developmental and cross-cultural aspects of arithmetic, as well as the neuroscience of number concepts and arithmetic. There are many theories that differ in detail and sometimes in ...